Establishment Reference Intervals Using the Kosmic Algorithm for Hemoglobin Levels and Platelet, Red Blood Cell, and White Blood Cell Counts - Chunyan Liu; Zhaohui Deng; Yingbo Song; Wenli Wu; Yan Li; Fang Yang; Huimin Liu; Xin Zhang (Journal of Clinical Laboratory Analysis, 2026)
ABSTRACT Introduction Reference intervals ( RIs ) for complete blood count ( CBC ) are crucial for assessment of overall health status and effective diagnosis of diseases. However, the RI data for CBC currently used in clinical practice in China are mainly derived from the Han Chinese population and are not stratified by ethnicity. This study aimed to calculate RIs for red blood cell count ( RBC ), hemoglobin ( HGB ), white blood cell count ( WBC ), and platelet count ( PLT ) among local populations based on ethnicity and sex in Xinjiang, China, using an indirect method to help clinicians better explain patient status in multiethnic populations. Methods We analyzed data from 5679 individuals. We used Tukey's test to eliminate outliers based on ethnicity, sex, and age. Subgroup stratification of RIs for RBC, WBC, PLT, and HGB was determined according to a standard deviation ratio threshold. Total RIs and ethnicity‐ and sex‐specific RIs for these parameters were calculated using the kosmic algorithm. Results The RIs for RBC and HGB must be stratified by sex, while those for PLT must be stratified by ethnicity. However, the RI for WBC does not require stratification. Sex‐stratified RIs for RBC and HGB in men showed higher upper limits than those in women. The RI for Uyghur individuals had a higher upper limit than that for Han Chinese individuals. Conclusions Personalized RIs for CBC provide a laboratory basis for disease diagnosis and treatment and health assessment among adults in Xinjiang.